The small‐molecule 3G11 inhibits HIV‐1 reverse transcription. (15th November 2016) - Opp, Silvana; Fricke, Thomas; Shepard, Caitlin; Kovalskyy, Dmytro; Bhattacharya, Akash; Herkules, Frank; Ivanov, Dmitri N.; Kim, Baek; Valle‐Casuso, Jose; Diaz‐Griffero, Felipe
Abstract : The small‐molecule 6‐( tert ‐butyl)‐4‐phenyl‐4‐(trifluoromethyl)‐1H, 3H‐1, 3, 5‐triazin‐2‐one (3G11) inhibits HIV‐1 replication in the human T cell line MT‐2. Here, we showed that 3G11 specifically and potently blocks HIV‐1 infection. By contrast, 3G11 did not block other retroviruses such as HIV‐2, simian immunodeficiency virus (SIVmac ), bovine immunodeficiency virus, feline immunodeficiency virus, equine infectious anemia virus, N‐tropic murine leukemia virus, B‐tropic murine leukemia virus, and Moloney murine leukemia virus. Analysis of DNA metabolism by real‐time PCR revealed that 3G11 blocks the formation of HIV‐1 late reverse transcripts during infection prior to the first‐strand transfer step. In agreement, an in vitro assay revealed that 3G11 blocks the enzymatic activity of HIV‐1 reverse transcriptase as strong as nevirapine. Docking of 3G11 to the HIV‐1 reverse transcriptase enzyme suggested a direct interaction between residue L100 and 3G11. In agreement, an HIV‐1 virus bearing the reverse transcriptase change L100I renders HIV‐1 resistant to 3G11, which suggested that the reverse transcriptase enzyme is the viral determinant for HIV‐1 sensitivity to 3G11. Although NMR experiments revealed that 3G11 binds to the HIV‐1 capsid, functional experiments suggested that capsid is not the viral determinant for sensitivity to 3G11. Overall, we described a novel non‐nucleoside reverse transcription inhibitor that blocks HIV‐1 infection. Abstract : 3G11 binds to capsid and blocks HIV‐1 reverse transcription during infection.